2005
DOI: 10.1080/10790268.2005.11753832
|View full text |Cite
|
Sign up to set email alerts
|

Baclofen Pump Intervention for Spasticity Affecting Pulmonary Function

Abstract: Introduction: Muscle spasticity may adversely affect pulmonary function after spinal cord injury (SCI). However, there is limited information regarding the treatment of spasticity as a determinant of pulmonary function. This study presents the case of a man with C4 tetraplegia who had severe spasticity and difficulty weaning from ventilatory support.Methods: Case presentation.Results: Severe spasticity likely contributed to respiratory compromise in this patient. Successful and rapid weaning from the ventilato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…It has been shown that most human SCI lesions are to some degree incomplete [6, 70, 71] which is also true for respiratory motor control [85]. Further, the unintended and unwanted muscle activity or spasticity experienced by many people with spinal cord injuries can also impair respiratory function [9, 69, 86]. Thus, the evaluation of motor control of respiration is as yet not well developed [69].…”
Section: Respiratory Motor Control After Scimentioning
confidence: 99%
“…It has been shown that most human SCI lesions are to some degree incomplete [6, 70, 71] which is also true for respiratory motor control [85]. Further, the unintended and unwanted muscle activity or spasticity experienced by many people with spinal cord injuries can also impair respiratory function [9, 69, 86]. Thus, the evaluation of motor control of respiration is as yet not well developed [69].…”
Section: Respiratory Motor Control After Scimentioning
confidence: 99%
“…Some studies indicated that muscle spasticity may also affect respiration after SCI (135,136). For example, in a recent case study, baclofen was administered to a C4-level patient who was unable to wean from the ventilator (136).…”
Section: Drug Administrationmentioning
confidence: 99%
“…The efficacy of ITB therapy for severe spasticity is well known . Patients with acute CSCI often require mechanical ventilation . It has been reported that patients with spastic diplegic CP have reduced FVC and FEV1.0 , and it is well understood that these patients are at high risk for aspiration pneumonia .…”
Section: Discussionmentioning
confidence: 99%
“…However, these patients sometimes experience subjective respiratory improvement after ITB initiation. Some were reported that the ITB therapy improved sleep apnea in a patient with CP and that it facilitated earlier ventilatory weaning in a patient with SCI . However, it was also reported that ITB therapy did not modify lung function tests in patients with various types of spasticity .…”
Section: Introductionmentioning
confidence: 99%